Business, Family, and Frontier: Reading Family Histories of Frontier Business Community - Ali, Faiz; Malik, Tasleem (The Journal of Humanities & Social Sciences, 2024)
Family histories of the frontier business community constitute a genre on the interstices of history and literature. They offer resources for and sites of reimagining frontier scholarship, the northwest frontier in this case. They represent the voices of those frontier communities who, despite having a critical role in the social, political, and economic history of the colonial frontier, have remained mainly excluded or left to low margins. Literature from and regarding such communities has yet to be addressed and is limited in scope and scholarship. To bring ‘commercial’ construction of frontier, this paper undertakes a critical reading of five selected texts exploring three aspects - context, nature, and contribution of these works. The study concludes that such indigenous narratives constitute useful sources for and offer insights into future research on the significant role of commercial communities in critical reading and understanding of the colonial frontier.